Cuando la memoria también habla del porvenir. El flujo temporal en los discursos de reivindicación identitaria en Aguacatenango (Chiapas) - Marie Chosson (Journal de la Société des Américanistes)
For some of the population of the Tseltal village of Aguacatenango, the official request for administrative independence triggered a collective deliberation process aimed at drafting a document that would demonstrate to the external authorities the village group’s social coherence and existential continuity. Stemming from this desire to legitimize the exercise of authority over what they considered their territory, this document stating their claims was constructed by mobilizing the collective memory. This contribution aims to highlight a particular perception of temporality, by analyzing how, in their discourse and according to their intentions, the Tseltal traditionalists of Aguacatenango organize intertwined references to long-term time, memory of life and forecasts of the future. This analysis of the modalities of discursive strategies will shed light on Tseltal representations of temporal flow and the role attributed to human beings in maintaining its balance.